Cochlear implantation in a patient with Usher's Syndrome - (:unkn) unknown (My University, 2002)
Usher's Syndrome is an autosomal recessive disorder characterized by congenital hearing loss and retinitis pigmentosa. Usher's Syndrome patients with severe to profound sensorineural hearing loss can be considered as candidates for cochlear implantation. This case study reports a deaf-blind with Usher's Syndrome who received a cochlear implant, the audiological evaluation is presented and the therapy sessions are discussed. The patient demonstrated good performance overtime after the implantation including open set speech understanding and telephone use.
Keywords: Cochlear implant; Usher's Syndrome